Lugalzagesi: the first emperor of Mesopotamia? - Kesecker, Nshan Thomas (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
In the middle of the 24th century BC, Sargon of Akkad defeated King Lugalzagesi of Uruk (c. 2350) and established Sargonic rule over Mesopotamia. His successors, Rimush, Manishtusu and Naramsin would expand and consolidate Sargon’s gains, until the crumbling of the state under Sharkalisharri. The deeds of the Sargonic Dynasty were acknowledged to the point that Sargon and Naramsin were immortalised in the historical literary tradition of Mesopotamia (and Anatolia) for millennia. However, several questions regarding the political history of Early Dynastic (c. 2900-2350) and Sargonic (c. 2350-2250) Mesopotamia remain. Were the Akkadian kings the first to envision a Mesopotamian Empire? This study seeks to analyze the political and ideological origins of empire-building in Mesopotamia, focusing on the late ED III period and the Sargonic transition. The contributions of Lugalzagesi in the development of a Mesopotamian ‘World Empire’ have been overlooked in many accounts of the political development of the region. By analyzing the political history, historical memory, and royal ideology of Lugalzagesi and his contemporaries, it can be observed that the first empire of the historical period in Mesopotamia was the state of Lugalzagesi.